The valley and the vision - Dale, Stanley, 1916-1968; Regions Beyond Missionary Union (London, UK Regions Beyond Missionary Union, 1970)
Plates, illustrations, maps.
Brethren writer and missionary. Completed posthumously. Booklet has been attached inside back cover : Return to Silvam / Don Richardson
Keywords: Missions -- West Irian; Brethren movement -- missionary martyrs -- Irian Jaya